Environmental aspects of the Hotel business - Marshalenko, Marianna (My University, 2018)
Environmental aspects of the Hotel business are revealed.
Keywords: туризм; готельний бізнес; екологія; кафедра готельно-ресторанної справи; гостиничный бизнес; экология; tourism; hotel business; ecology